Pengukuran Tingkat Kapabilitas Teknologi Informasi Pada Perum BULOG Kantor Cabang Lhokseumawe - Angga Pratama; Rumagit, Bella Fadillah Rahmah; Muhammad Ikhwani (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2024)
Information technology provides great benefits to every organization by facilitating decision making and streamlining operational activities and daily business processes. Perum BULOG Lhokseumawe Branch Office is a company that implements information technology. COBIT 2019 is the framework used in this research which has standards for implementing information technology governance. References from annual reports can be used as a reference in analyzing the level of information technology capabilities in companies using the COBIT 2019 design factor toolkit. After analyzing the questionnaire distributed using a Likert scale, process objectives that can be evaluated. The calculation results are obtained with the following capability level results, APO03 is at capability level 1 and has a gap of 2, APO12 is at capability level 2 and has a gap of 1, APO13 is at capability level 3 and has no gap, namely 0, BAI01 is at capability level 2 and has a gap of 1, BAI02 is at capability level 1 and has a gap of 2, BAI03 is at capability level 1 and has a gap of 3, BAI06 is at capability level 1 and has a gap of 3, BAI07 is at capability level 2 and has a gap worth 1, BAI10 is at capability level 1 and has a gap worth 3. Objectives that have a gap will be given recommendations. Â  Keywordsâ€”Information Technology, COBIT 2019, Capability Level, gap